2001
DOI: 10.1007/s00441-001-0489-4
|View full text |Cite
|
Sign up to set email alerts
|

Bile canalicular barrier function and expression of tight-junctional molecules in rat hepatocytes during common bile duct ligation

Abstract: Tight junctions of hepatocytes form the intercellular barrier between the blood circulation and bile flow. We focused on early stages of common bile duct ligation to observe changes in tight junctions without the irreversible changes seen after lengthy ligation. Common bile ducts of 12-week-old male rats were ligated for 6 h because, at this time point, no histological changes were observed. Serum bilirubin and bile acid levels began to increase 3 h after ligation and were restored to the control level immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Furthermore, the canalicular protein Ca 2ϩ -Mg 2ϩ -ATPase was shown to undergo endocytic internalization and selective redistribution to the lateral membrane in chronic, experimental obstructive cholestasis (30), a model that is also accompanied by increased tight junctional permeability (32) and endocytic internalization of Mrp2 (23). Irrespective of the mechanism, endocytic internalization and selective relocalization to the lateral membrane under sustained E 2 17G cholestasis were not restricted to Mrp2, as a similar phenomenon was observed for DPPIV.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, the canalicular protein Ca 2ϩ -Mg 2ϩ -ATPase was shown to undergo endocytic internalization and selective redistribution to the lateral membrane in chronic, experimental obstructive cholestasis (30), a model that is also accompanied by increased tight junctional permeability (32) and endocytic internalization of Mrp2 (23). Irrespective of the mechanism, endocytic internalization and selective relocalization to the lateral membrane under sustained E 2 17G cholestasis were not restricted to Mrp2, as a similar phenomenon was observed for DPPIV.…”
Section: Discussionmentioning
confidence: 54%
“…Immunofluorescence staining of cryosections of rat liver indicated a linear distribution of 7H6 around the canalicular lumen 47 . Further studies demonstrated the expression of claudin 1, 2 and 3 in rat liver 48 . In zebra fish, the expression of claudin 15-like b protein was found to be essential for bile duct morphogenesis 49 .…”
Section: Tight Junctions Of Bile Duct Epitheliummentioning
confidence: 91%
“…9) In such cases, changes in the pharmacokinetics of the drug could be partly predicted from the results of the detailed studies of transporter expression in the liver and kidneys and from in vitro studies in isolated cells. Nevertheless, the existence of other mechanisms involved in the pathophysiology of cholestasis such as paracellular leakage through an impaired blood-biliary barrier (tight-junction connection of hepatocytes) or decreased perfusion of organs 10) makes such predictions less accurate and raises the need for data from in vivo kinetic studies.…”
mentioning
confidence: 99%